Do people with knee osteoarthritis use guideline-consistent treatments after an orthopaedic surgeon recommends nonsurgical care? A cross-sectional survey with long-term follow-up. Issue 2 (June 2022) - Mazzei, D.R.; Whittaker, J.L.; Kania-Richmond, A.; Faris, P.; Wasylak, T.; Robert, J.; Hawker, G.; Marshall, D.A.
Abstract: Objective: Describe "usual care" patterns of education, exercise, weight management, pain medication and other nonsurgical treatments for knee osteoarthritis (OA) in people recommended for nonsurgical care by an orthopaedic surgeon. Methods: We used a telephone-administered questionnaire to capture treatments people with knee OA used over the three to six years after an orthopaedic surgeon recommended nonsurgical care. The primary outcome, guideline-consistent nonsurgical treatments, was an aggregate measure defined as using education, exercise, weight management, and at least one recommended medication. Secondary outcomes were first-line (education, exercise, and weight management) and guideline-inconsistent treatments (orthoses, opioids, hyaluronic acid, platelet rich plasma, and stem cell therapy). Multivariable robust Poisson regression assessed the association between participant characteristics and use of guideline-consistent, first-line and guideline-inconsistent treatments. Results: 479 people were invited and 250 participated (52%). Participants were 58% female with a mean age 66.2 years. Participants received education by a healthcare professional (64%), exercised regularly (74%), used weight management (38%), and used recommended pain medications (91%). All guideline-consistent nonsurgical treatments were used by 19% of participants, 19% of participants used first-line treatments, and 42% used guideline-inconsistent treatments. Over six years, 34% had another consult then underwent arthroplasty. Older participants were less likely to use any treatment. People without post-secondary education were less likely to use first-line treatments (RR 0.54, 95% CI: 0.30–0.96), and females were less likely to use guideline-inconsistent treatments (RR 0.62, 95% CI:0.47–0.81). Conclusions: Nonsurgical usual care for people with knee OA was not consistent with international clinical guidelines.